PENGARUH LATIHAN TWISTINK TRUNK CURL TERHADAP KEKUATAN DAN DAYA TAHAN OTOT PERUT PADA ATLET PUTRI SHORINJI KEMPO RUMBAI PEKANBARU - Rasti, Rika Rasti; Agust, Kristi Agust; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The issues raised in this studyis"Whether effect of exercise twistink trunk curl To Power and endurance abdominal muscle In the women atlets Shorinji Kempo Rumbai Pekanbaru?".This research is experimental research that aims to find out the effect of exercise twistink trunk curl To Power and endurance abdominal muscle In the women’s atlet  Shorinji Kempo Rumbai Pekanbaru. Population used was the entire women’s atlet  Shorinji Kempo Rumbai Pekanbaru as many as 8 people. This study uses total sampling technique the entire population sampled. Based on the determination of sample, the sampel of 8 people. As the independent variable (x) was training twistink trunk curl while the dependent variable (y) is the Power and endurance abdominal muscle. Were obtained and collected through the free test and post test before and after exercise twistink trunk curl using a meansuring tool that is sit up 30 second Test. The methodof processing data using descriptive statistics calculation sand to test the hypothes is using the t test.The hypothesis proposed in this studyis the effect ofexercise twistink trunk curl To Power and endurance abdominal muscle In the women atlets Shorinji Kempo Rumbai Pekanbaru.The result softhe ttest produced 20,44 and 1,895ttableat thesignificant leve lof 0.05. Meansttest>t table .So, the conclusion isthere is asignificant effect of exercise twistink trunk curl To Power and endurance abdominal muscle In the women’s atlet  Shorinji Kempo Rumbai Pekanbaru and Ha be accepted. KeyWords: Twistink Trunk Curl. Power and endurance abdominal muscle